Rancangan Aplikasi Autentikasi Surat Digital dengan Metode One Time Password SHA-512 Berbasis Android - Salwa Kamila; Lindawati Lindawati; Mohammad Fadhli (Universitas Budi Darma, 2022)
Some administrative procedures in many institutes are still carried out conventionally, which is deemed less efficient and takes much time. On the other hand, communication with other parties requires a process of exchanging information, so a system is needed to confirm the validity of the information. Therefore, a digital letter system that can prove the validity of the information gained through the digital media right from the party concerned is developing. This can be overcome using the authentication method. Adding One Time Password (OTP) as an authentication method that employs one temporary password key can be the solution. This study uses the One Time Password (OTP) method as a validation system and the SHA-512 algorithm as an OTP code generator to generate random codes. This system leverages android technology on mobile to ease access to the correspondence administration system to make it easier to visit with features that prioritize information and access speed. This application is implemented at the State Polytechnic of Sriwijaya to improve the administrative process to run more effectively. The black box testing revealed that all available menus and features were appropriate, and the application already had a system that functions according to user needs. Moreover, in the One Time Password generation test with the SHA-512 algorithm, it was determined that the average response time for generating the OTP code was 4.4 seconds in 15 trials, which can be considered fairly accurate.